2019
DOI: 10.5812/pedinfect.87961
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Class I Integron Gene Cassettes and the Multidrug-Resistance in Extended -Spectrum β-Lactamase Producing Isolates of Escherichia coli

Abstract: Background: Integron is an important element in creating multi-drug resistant (MDR) bacteria. This study evaluated the relationship of class I integron and antibiotic resistance in extended-spectrum beta-lactamase producing (ESBL) isolates of Escherichia coli (E. coli). Methods: A total of 66 ESBL-producing E. coli were isolated from urinary tract infection in Kermanshah and their antimicrobial susceptibility was assessed. The incidence of class I integron was determined in isolates using PCR. The class I inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The spread of mobile genetic elements among different strains may have resulted in the antimicrobialresistant phenotypes observed in this study. Akya et al in Iran found that the highest rate of resistance was noticed for ceftriaxone, cefotaxime, and cotrimoxazole [23] which agrees with a previous study in Iran [24]. A higher percentage of MDR (87.9%) among E. coli isolates was reported by Al-Hammadi and colleagues in Yemen [25].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The spread of mobile genetic elements among different strains may have resulted in the antimicrobialresistant phenotypes observed in this study. Akya et al in Iran found that the highest rate of resistance was noticed for ceftriaxone, cefotaxime, and cotrimoxazole [23] which agrees with a previous study in Iran [24]. A higher percentage of MDR (87.9%) among E. coli isolates was reported by Al-Hammadi and colleagues in Yemen [25].…”
Section: Discussionsupporting
confidence: 78%
“…It was found that 88.5%, 83.6%, 83.6% and 81.9% out of 61 MDR ESBL producing E. coli isolates that harbored class I integrons were significantly resistant to aztreonam, ceftazidime, cefotaxime and ciprofloxacin, respectively (p<0.05). Similarly, Akya et al observed a significant correlation between antibiotic resistance to co-trimoxazole (P = 0.01), streptomycin (P= 0.018) and ceftazidime (P=0.032) with class I integrons, which emphasizes the association between resistant genes and this class of integron [23].…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…42 About 9% of the sequenced bacterial genomes contain integrons, and the class I integron platform is the most prevalent one and had received the most reports among clinical bacteria, and is still the subject of several investigations. 43 The prevalence rate of class I integron in this study was 54.2%, there are many studies all over the world that record different prevalence rates of integron classes specifically class I integron among Enterobacteriaceae [44][45][46][47][48] this variation might be due to difference in the sample population, geographical distribution, and groups which had been selected for taking urine samples.…”
Section: Discussionmentioning
confidence: 68%